2009
DOI: 10.1155/2009/104647
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Serum Cotinine Levels of Smokers

Abstract: Abstract. The purpose of this study was to estimate black/white differences in cotinine levels for current smokers of both sexes, and to explore the potential contribution of mentholated cigarettes to these differences. Sera from 255 current smokers sampled from Southern Community Cohort Study participants (65 black men, 65 black women, 63 white men, 62 white women) were analyzed for cotinine, and linear regression was used to model the effect of race on cotinine level, adjusting for the number of cigarettes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
2
29
1
Order By: Relevance
“…Also, on an average, the specific menthol brand and subbrands black smokers smoked had a higher FTC nicotine levels than the nonmenthol brands (the preferred type of cigarette smoked by whites) smoked by white smokers. At least 2 previous studies have found higher cotinine concentrations among smokers of mentholated cigarettes (20,21), whereas others did not (22)(23)(24)(25)(26)(27). In a recent study a Model 1: cpd þ continuous nicotine þ sex þ continuous weight.…”
Section: Discussionmentioning
confidence: 93%
“…Also, on an average, the specific menthol brand and subbrands black smokers smoked had a higher FTC nicotine levels than the nonmenthol brands (the preferred type of cigarette smoked by whites) smoked by white smokers. At least 2 previous studies have found higher cotinine concentrations among smokers of mentholated cigarettes (20,21), whereas others did not (22)(23)(24)(25)(26)(27). In a recent study a Model 1: cpd þ continuous nicotine þ sex þ continuous weight.…”
Section: Discussionmentioning
confidence: 93%
“…However, despite later initiation, black adults smoke at rates similar to whites (black men, 23.9%; black women, 19.2%; white men, 24.5%; white women, 19.8%) [23]. This is of particular concern because evidence suggests that racial differences in nicotine exposure (nicotine intake per cigarette is 30.0% greater) and metabolism of tobacco (slower clearance of nicotine) place black smokers, compared with white smokers, at a higher risk for tobacco-related diseases [24,25]. Blacks also have a lower rate of successful quitting [4,26].…”
Section: Blacks Are At Risk For Continued Smoking and Poor Cessation mentioning
confidence: 99%
“…Some studies have shown that menthol cigarette use is associated with increased biomarkers of intake of tobacco smoke constituents (Clark, Gautam, & Gerson, 1996;Williams et al, 2007), whereas other studies have found no differences in levels of tobacco biomarkers by cigarette type (Ahijevych, Gillespie, Demirci, & Jagadeesh, 1996;Benowitz, Herrera, & Jacob, III, 2004;Heck, 2009;Muscat et al, 2009;Mustonen et al, 2005;Signorello, Cai, Tarone, McLaughlin, & Blot, 2009;Tobacco Products Scientific Advisory Committee [TPSAC], 2011;Wang et al, 2010). In a study of 161 Black and White smokers, menthol cigarettes were associated with higher cotinine levels and carbon monoxide concentrations after adjusting for race, cigarettes per day, and mean amount of cigarettes smoked (cigarettes smoked per day × average length [in millimeters] of each cigarette smoked; Clark et al, 1996).…”
Section: Discussionmentioning
confidence: 99%